2015
DOI: 10.1371/journal.pone.0127189
|View full text |Cite
|
Sign up to set email alerts
|

Trait Anxiety Has Effect on Decision Making under Ambiguity but Not Decision Making under Risk

Abstract: Previous studies have reported that trait anxiety (TA) affects decision making. However, results remain largely inconsistent across studies. The aim of the current study was to further address the interaction between TA and decision making. 304 subjects without depression from a sample consisting of 642 participants were grouped into high TA (HTA), medium TA (MTA) and low TA (LTA) groups based on their TA scores from State Trait Anxiety Inventory. All subjects were assessed with the Iowa Gambling Task (IGT) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 74 publications
3
34
1
1
Order By: Relevance
“…The present results are consistent with previous research relating trait anxiety with risk-taking behaviors (Aarts & Pourtois, 2012;Charpentier et al, 2017;Xu et al, 2013;Zhang et al, 2019). It should be noted that the BART is a relatively simple task; high trait anxiety has also been associated with general impairment in risky decision-making tasks with a high executive function component (Zhang et al, 2015(Zhang et al, , 2019, possibly due to executive system impairment in high trait anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results are consistent with previous research relating trait anxiety with risk-taking behaviors (Aarts & Pourtois, 2012;Charpentier et al, 2017;Xu et al, 2013;Zhang et al, 2019). It should be noted that the BART is a relatively simple task; high trait anxiety has also been associated with general impairment in risky decision-making tasks with a high executive function component (Zhang et al, 2015(Zhang et al, , 2019, possibly due to executive system impairment in high trait anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with impairments in executive control, Zhang and colleagues (2019) found that people high in trait anxiety prefer immediate rewards in intertemporal choice tasks. Zhang, Wang, Zhu, Yu, and Chen (2015) found that performance of those high in trait anxiety was associated with a general decisionmaking impairment in the Iowa gambling task.…”
Section: Role Of Frontoparietal Attentional Control Mechanismsmentioning
confidence: 97%
“…The CTD is of great importance at this stage. Emotions affect a series of critical cognitive tasks and outputs, including data processing, judgment, and decision-making (Bachkirov, 2015;Brosch, Scherer, Grandjean, & Sander, 2013;Thiel, Connelly, & Griffith, 2012;Zhang, Wang, Zhu, Yu, & Chen, 2015). In the literature, there are studies indicating that anxiety affects decision-making (Miu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…humans with high anxiety, decision-making is also impaired in presence of ambiguous choices [33,51,88]. The elevated platform with downward slopes, unlike the plus-maze, light/dark box, and the open-field, does not provide a refuge or a shelter, which promote safety and security over risk taking [24,21].…”
Section: D 21mentioning
confidence: 99%